2018
DOI: 10.1017/s1041610218001886
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive impairment: some steps forward

Abstract: There is no doubt that the term mild cognitive impairment (MCI) has become popular in the last decades (Flicker et al., 1991; Petersen et al., 1997). A superficial quantification of the publications that include said term in the title in the Web of Science yields 9,334 citations, including 6,553 articles, 667 reviews, 187 editorials, 37 books, and 249 patents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A survey developed among expert neurologists showed that 90% of them recognize MCI as a clinical diagnostic entity 12 . In WoS, MCI yields more than 650 reviews and 37 books 13 …”
Section: Methods and Main Bibliographic Findingsmentioning
confidence: 99%
“…A survey developed among expert neurologists showed that 90% of them recognize MCI as a clinical diagnostic entity 12 . In WoS, MCI yields more than 650 reviews and 37 books 13 …”
Section: Methods and Main Bibliographic Findingsmentioning
confidence: 99%